Kemungkinan Mekanisme Peran Zink dalam Patogenesis Covid-19 - Moch Ikhsan Juliansyah; Lisa Adhia Garina (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. This study was conducted to gather sufficient information on the possible mechanism of the role of zinc in the pathogenesis of COVID-19. The method used in this study is a literature study that collects several previous studies to determine the possible mechanism of the role of zinc in the pathogenesis of COVID-19. The results of this study indicate that there are various possible mechanisms of the role of zinc in the pathogenesis of COVID-19 such as preventing virus entry by increasing epithelial integrity, increasing the ability of mucociliary clearance mechanisms, decreasing ACE-2 receptor expression, preventing viral replication by inhibiting RNA polymerase, eliminating viruses by destabilizing them. viral envelope, regulates the immune system such as activation of natural killer cells, cytotoxic T cells, amplifies B cell receptor signaling, antibody formation and regulates regulatory T cell activity and expression of nuclear factor kappa B to maintain a balanced immune response. Thus, it can be said that zinc has a possible role mechanism in the pathogenesis of COVID-19 by preventing the virus from entering, making virus replication, eliminating the virus, and maintaining a balance of immune responses when someone is exposed to COVID-19. Abstrak. Studi ini dilakukan untuk mengumpulkan informasi yang cukup terhadap kemungkinan mekanisme peran zink dalam patogenesis COVID-19. Metode yang digunakan dalam studi ini adalah studi literatur yang mengumpulkan beberapa penelitian terdahulu untuk mengetahui kemungkinan mekanisme peran zink dalam patogenesis COVID-19. Hasil dari studi ini menunjukan adanya berbagai kemungkinan mekanisme peran zink dalam patogenesis COVID-19 seperti mencegah virus masuk dengan meningkatkan integritas epitel, meningkatkan kemampuan mekanisme mucociliar clearance, menurunkan ekspresi reseptor ACE-2, mencegah replikasi virus dengan menghambat RNA polimerasenya, mengeliminasi virus dengan mendestabilisasi envelop virus, meregulasi sistem imun seperti aktivasi sel natural killer, sel T sitotoksik, memperkuat penyinalan reseptor sel B, pembentukan antibodi dan meregulasi aktivitas sel T regulator dan ekspresi nuclear factor kappa B untuk mempertahankan keseimbangan respon imun. Dengan demikian dapat disimpulkan bahwa zink memiliki kemungkinan mekanisme peran dalam patogenesis COVID-19 dengan cara mencegah virus masuk, mencegah replikasi virus, mengeliminasi virus dan menjaga keseimbangan respon imun pada saat seseorang terkena COVID-19.